Indigenous studies in Argentina: anthropology, history and ethnohistory from the 1980s - Salomon Tarquini, Celia Claudia (2018)
This paper analyzes the development of studies concerning indigenous peoples in Argentina during the last thirty years, since the mid 1980?s, when the return of democracy allowed for substantial changes in academic spaces and indigenous peoples movements started to gain visibility in this country. A first section is devoted to a brief history of native peoples in the country and state policies to provide adequate context, followed by a second section which addresses studies from anthropology, ethnohistory and history (or historiography), paying special attention to social conditions and academic spaces built to foster new perspectives. A third section will focus on the case of studies concerning indigenous peoples in the Pampas and Patagonia. Our main sources for this section are academic papers, conference abstracts, semi-structured interviews with historians, anthropologists and archaeologists and their curricula vitae. The methodological approach is mostly qualitative and techniques of network analysis and documentary observation are used.